Revival of the Silk Road legacy. Examining how China uses history to legitimize its ‹‹Belt and Road Initiative›› - AMARASINGHE, Punsara (Historia i Świat, 2023)
This article is an interdisciplinary inquiry into the usage of historical silk routes by the Chinese as a popular narrative for the modern BRI. While looking at the archaeological trace, the historiography and other dimensions, this article would unfold how the nostalgia on the ‘Silk Routes’ have been rejuvenated for an ambitious geopolitical project. Taking both land and maritime silk routes into the consideration, this paper would further consider the position of historical narratives for the geopolitical ambitions of the 21st century.